Neuropathic ulcers in leprosy: clinical features, diagnosis and treatment. (1st June 2022) - Serrano-Coll, Héctor; Cardona-Castro, Nora
Abstract : Leprosy is a neglected disease caused by Mycobacterium leprae and Mycobacterium lepromatosi s, and is related to significant disabilities resulting from the neural damage generated by this mycobacteria. Neuropathic ulcers—lesions that can appear at the plantar and extra-plantar levels—are one such disability, and diagnosis requires an adequate dermatological, neurological and microbiological evaluation. The treatment of these lesions is based on a multidisciplinary approach that includes debridement of the necrotic tissue, controlling infections, reducing pressure areas, optimising blood flow, and nerve decompression. This review aims to describe the clinical features, diagnostic methods and treatment of neuropathic ulcers in leprosy. The diagnostic methods and medical management used in leprosy ulcers are based on those used for diabetic foot. This requires radical change as these diseases are immunologically and physiologically very different.